One weighs a ton : includes 10 lift the flaps and touch- and-feels! - Yoon, Salina (Philadelphia, PA : RP Kids, 2009)
Rhymes for the numbers one to ten plus factual information about certain animals.
Cover title; publisher information from p. [4] of cover.
"Includes 10 lift the flaps and touch-and-feels!" -- Cover.
Keywords: Counting; Animals; Lift-the-flap books; Textured books